Prescribing Patterns of Oral Opioid Analgesic for Long Bone Fracture at Tertiary Care Children's Hospital Emergency Departments and Urgent Cares. Issue 12 (December 2021) - Wang, George Sam; Reese, Jennifer; Bakel, Leigh Anne; Leonard, Jan; Bos, Tod; Bielsky, Alan; Nickels, Sarah; Bajaj, Lalit
Abstract : Objectives: Disparities in opioid prescribing in children can lead to underprescribing and poorly controlled pain. On the contrary, unnecessary overprescribing can increase the risk for misuse, abuse, and diversion. The primary objective of this study was to compare the demographics and clinical characteristics of children with an extremity fracture who did and did not receive an opioid prescription from a tertiary care children's hospital. Methods: This was a retrospective cohort study of children younger than 22 years with extremity fracture evaluated at a tertiary care children's hospital emergency department (ED) and surrounding satellite locations (3 EDs and 4 urgent cares), from January 1, 2017, to December 31, 2017. Results: There were 3325 patients younger than 22 years who were seen for evaluation of an extremity fracture. The overall median age of patients was 8 years (interquartile range [IQR], 4–11), and 1976 (59.4%) were male. Patients with extremity fractures who received opioid analgesics were older than those who did not receive opioids (median age of 10 years [IQR, 6–13 years] vs 7 years [IQR, 4–11 years], P < 0.001). There was a significant difference found between insurance types, specifically those patients receiving Medicaid and private insurance. Patients who received opioid analgesics had a higher initial pain score (7 [IQR, 4–9] vs 5 [IQR, 2–7], P < 0.001), were more likely to have an physician (MD/DO) provider ( P < 0.001), and were more likely to present to the ED ( P < 0.001). Conclusions: Younger patients, patients with Medicaid insurance, patients treated by an advanced care provider, and patients who presented to an urgent care were less likely to receive opioid analgesics upon discharge. These findings demonstrate that more standardization and guidance on opioid prescribing are needed in pediatrics, to both adequately treat pain and reduce harms from overprescribing of opioid analgesics.